Genome-wide selection analysis identifies genes associated with mandibular defects in Duolang sheep - Cao, Hang; Chen, Qiuming; Liu, Ling-Ling; Liu, Wu-Jun (Frontiers in Veterinary Science, 2026)
IntroductionBrachycephaly is characterized by a conspicuously shortened craniofacial structure. While it is a defining trait in certain species such as Bulldogs, Persian cats, Niata cattle, Anglo-Nubian goats, and Middle White pigs, it may also represent a pathological condition. In Duolang sheep, brachycephaly is strikingly pronounced and may arise from distinct genetic and developmental mechanisms linked to breed history. This condition, often accompanied by mandibular prognathism, predisposes affected animals to health problems including brachycephalic airway obstruction syndrome, nasal blockage with dyspnea, and feeding difficulties. Duolang sheep, a dominant indigenous breed in southern Xinjiang, China, comprise approximately two million individuals, nearly 10% of which exhibit this heritable defect. Such a high prevalence poses a significant challenge to genetic improvement programs in local populations. Elucidating the genetic basis of this phenotype and identifying candidate genes is therefore essential.MethodsTo characterize the craniofacial phenotype, we obtained X-ray measurements of maxillary length, mandibular length, and incisor angle. Affected sheep displayed significantly shorter maxillae and longer mandibles compared with controls (p < 0.05), whereas incisor angle showed no significant difference. Here, we performed whole-genome resequencing of two phenotypically distinct Duolang sheep cohorts and analyzed genomic architecture and variation patterns using a selective sweep approach.ResultsCandidate regions under strong selection were identified by Fst and π-ratio analyses. Gene annotation revealed functionally relevant candidates associated with skeletal growth and development (MTX2, FGF12, IGF, PPARGC1A, LIPC, LY86, and IL33).DiscussionThese findings provide new insights into the genetic basis of brachycephaly in Duolang sheep and offer strategies for genetic improvement, contributing to broader research on skeletal development and growth regulation in livestock.